BIO ANALYTICAL METHOD DEVELOPMENT AND VALIDATION OF FLUPENTIXOL AND NORTRIPTYLINE HCL IN RAT PLASMA AND ITS PHARMACOKINETIC STUDIES BY LCMS - VISALAKSHAMMA, V.; RAMUDU, B. SRI; SHARIF, SYED. KHASIM; BHARATH, P.; RAMACHANDRAN, D.; RAO, P. T. S. R. K. PRASADA; RAO, K. PRASADA (International Journal of Applied Pharmaceutics, 2025)
Objective: An easy, quick, precise, active and reproducible Liquid Chromatography Tandem Mass Spectrometry (LC-MS/MS) technique was developed for the bio-analytical method of flupentixol and nortriptyline HCl using zuclopenthixol as Internal Standard (IS). Methods: This article summarizes the recent progress on bio-analytical LC-MS/MS methods using Luna Phenyl Hexyl column (250x4.6 mm, 5µ) and organic mobile phase of Ammonium acetate pH-3.0/Formic acid and Acetonitrile in 70:30 v/v. 5 min of run time was used in the analysis. Results: The calibration curve was linear in the range of 5.0ng/ml to 200.0ng/ml (r2= 0.99988±0.006) for nortriptyline HCl and 0.25ng/ml to 10.0ng/ml (r2=0.99972±0.007) for flupentixol. Matrix effect, recovery and stability results were within the acceptable limit. An electrospray ionization source was used to study of nortriptyline HCl, flupentixol at m/z 300.8471 →73.2501, m/z 435.5225→103.4247 and m/z 400.9657→142.0087 for zuclopenthixol were ion pairs of mass analysis. Conclusion: The application denotes all the parameters of system suitability, specificity, linearity and accuracy are in good agreement with United States Food and Drug Administration (USFDA) guidelines and applied effectively for the investigation of pharmacokinetic studies in rat.